To scrape or not to scrape, this is dilemma. The post-API scenario and implications on digital research - Trezza, Domenico (Frontiers in Sociology, 2023)
This article aims is to investigate the potential impact of restricted social data access on digital research practices. The 2018 Cambridge Analytica scandal exposed the exploitation of Facebook user data for speculative purposes and led to the end of the so-called “Data Golden Age”, characterized by free access to social media user data. As a result, many social platforms have limited or entirely banned data access. This policy shift, referred to as the “APIcalypse”, has revolutionized digital research methods. Against this backdrop, we seek to explore how constraints on digital data access have altered research practices, whether we are truly in a post-API era with a radical change in data scraping strategies, and what shared and sustainable solutions can be identified for the post-API scenario. To address these questions, we surveyed a non-probabilistic sample of Italian researchers and analyzed their responses. This analysis offers insights into both the post-API research landscape and a potential way forward for following-the-medium research that prioritizes the quality, rather than quantity, of digital data. We conclude with a discussion of the future of digital research, particularly in light of new data access policies that should foster, rather than hinder, research efforts.